Image Guidance for Proton Therapy. Issue 5 (May 2018) - MacKay, R.I.
Abstract: Image-guided radiotherapy has an established role in all forms of radiotherapy treatment delivery. Proton therapy seeks to deliver superior dose distributions through utilising the Bragg peak to target tumour and avoid sensitive normal tissue. The Bragg peak and sharp falloff in dose delivered by proton therapy necessitate careful treatment planning and treatment delivery. The dose distribution delivered by proton therapy is particularly sensitive to uncertainty in the prediction of proton range during treatment planning and deviations from the planned delivery during the course of the fractionated treatment. Realising the superior dose distribution of proton therapy requires increased diligence and image guidance has a key role in ensuring that treatments are planned and delivered. This article will outline the current status of image guidance for proton therapy, particularly highlighting differences with regard to high-energy X-ray therapy, and will look at a number of future improvements in image-guided proton therapy.